Thermal Performance of Facades Based on Experimental Monitoring of Outdoor Test Cells in Tropical Climate - Letzai Ruiz-Valero; Juan Faxas-Guzmán; Julio Ferreira; Victor González; Néstor Guerrero; Francisco Ramirez (Salehan Institute of Higher Education, 2021)
The high cost of energy consumption in buildings highlights the importance of research focused on improving the energy efficiency of building’s envelope systems. It is important to characterize the real behavior of these systems to know the effectiveness in terms of energy reduction. Therefore, the aim of this paper is to characterize the thermal performance of facades based on experimental monitoring of outdoor test cells in tropical climate. To carry out this research, a case study was presented to compare two construction systems. One of them is a light façade (M1) and the other a reference façade (M2). A thermal simulation was performed for the opaque and glazed facades. In addition, several parameters were measured with different types of sensors, as well as environmental variables to evaluate the thermal and lighting behavior of multiple facades systems under real conditions. The findings show that light façade behavior was the opposite of what was expected, since by incorporating a window in the façade it has allowed solar radiation to increase the interior temperature in both modules. In the case of the light facade the penalization was higher than the reference facade, which has a lower thermal transmittance than M1. Doi: 10.28991/cej-2021-03091773 Full Text: PDF